An Empirical Study on the Digital Display Design of Intangible Cultural Heritages Based on Audience Satisfaction. (5th October 2022) - Zhang, Lei; Fu, Di; Zhao, Jinlong
Abstract : How the audience perceive the display of intangible cultural heritages (ICHs) and what are their psychological needs of ICH display are of great value to the display design of ICHs. This article carries out a questionnaire survey on the audience of the "Splendid China" ICH costume show and empirically analyzes the survey results. After constructing the American Customer Satisfaction Index (ACSI), the authors classified the psychological needs of customers for the on-site display of ICHs through analytical hierarchy process (AHP) and factor analysis, conducted the theoretical discussion, and verified the results with actual data. The research explores how should the digital display of ICHs be designed to satisfy the audience and provides a reference for China's ICH display designers. The research shows that the construction of a public satisfaction evaluation model for the digital display of ICHs is the key to satisfaction evaluation, there is ample room to improve public satisfaction with the digital display of ICHs, the dissemination of ICH can be strengthened through model construction, and personalized service is an effective way to promote the digital development of ICHs.